Drinking behaviour and water turnover rates of Antarctic fur seal pups: implications for the estimation of milk intake by isotopic dilution. - Lea, M-A; Bonadonna, F; Hindell, MA; Guinet, C; Goldsworthy, SD (2002)
The estimation of milk consumption in free-ranging seals using tritium dilution techniques makes the key assumption that the animals drink no pre-formed water during the experimental period. However, frequent observations of unweaned Antarctic fur seal pups drinking water at Iles Kerguelen necessitated the testing of this assumption. We estimated water flux rates of 30 pups (10.7¬¨¬±0.3 kg) in four experimental groups by isotopic dilution over 4 days. The groups were: (1) pups held in an open air enclosure without access to water to estimate fasting metabolic water production (MWP); (2) free-ranging pups not administered additional water; (3) pups held in an open air enclosure and given a total of 300 ml of fresh water to verify technique accuracy; and (4) free-ranging pups given 200 ml of fresh water. Pups without access to water exhibited water flux rates (20.5¬¨¬±0.8 ml kg‚Äöv†v¿1d‚Äöv†v¿1), which were significantly lower than those observed for the free-ranging group (33.0¬¨¬±1.7 ml kg‚Äöv†v¿1 d‚Äöv†v¿1). Mean estimated pre-formed water intake for the free-ranging experimental groups was 12.6 ml kg‚Äöv†v¿1 d‚Äöv†v¿1. Thus, MWP, measured as total water intake during fasting, may be significantly over-estimated in free-ranging Antarctic fur seal pups at Iles Kerguelen and at other sites and subsequently milk intake rates may be underestimated.